Drug therapy and catheter ablation for management of arrhythmias in continuous flow left ventricular assist device's patients: a Clinical Consensus Statement of the European Heart Rhythm Association and the Heart Failure Association of the ESC - Peichl, Petr; Bayes-Genis, Antoni; Deneke, Thomas; Chioncel, Ovidiu; deRiva, Marta; Crespo-Leiro, Maria Generosa; Frontera, Antonio; Gustafsson, Finn; Martins, Raphaël P; Pagnesi, Matteo; Maury, Philippe; Petrie, Mark C; et al. (Europace, 2024)
Left ventricular assist devices (LVADs) are an increasingly used strategy for the management of patients with advanced heart failure. Although these devices effectively improve survival, atrial and ventricular arrhythmias are common with a prevalence of 20-50% at one year after LVAD implantation. Arrhythmias predispose these patients to additional risk and are associated with considerable morbidity from recurrent implantable cardioverter-defibrillator shocks, progressive failure of the unsupported right ventricle, and herald an increased risk of mortality. Management of patients with arrhythmias and LVAD differs in many aspects from the general population heart failure patients. These include ruling out the reversible causes of arrhythmias that in LVAD patients may include mechanical irritation from the inflow cannula and suction events. For patients with symptomatic arrhythmias refractory to medical treatment, catheter ablation might be relevant. There are specific technical and procedural challenges perceived to be unique to LVAD-related ventricular tachycardia (VT) ablation such as vascular and LV access, signal filtering, catheter manoeuvrability within decompressed chambers, and electroanatomic mapping system interference. In some patients, the arrhythmogenic substrate might not be readily accessible by catheter ablation after LVAD implantation. In this regard, the peri-implantation period offers a unique opportunity to surgically address arrhythmogenic substrate and suppress future VT recurrences. This document aims to address specific aspects of the management of arrhythmias in LVAD patients focusing on anti-arrhythmic drug therapy and ablations.
Keywords: antiarytmika; Europe; Left ventricular assist device; Tachycardia, Ventricular; výsledek terapie; Heart Failure; Catheter Ablation; Heart-Assist Devices; funkce levé komory srdeční; lidé; srdeční selhání; Evropa; katetrizační ablace; konsensus; Treatment Outcome; Arrhythmias, Cardiac; Consensus; Risk Factors; Catheter ablation; podpůrné srdeční systémy; komorová tachykardie; Ventricular arrhythmia; rizikové faktory; Heart failure; Atrial fibrillation; Anti-Arrhythmia Agents; srdeční arytmie; Ventricular Function, Left; Humans